Investasi Emas Sebagai Alternatif Instrumen Keuangan Jangka Panjang Di Kabupaten Banjar - Nur Habibah; Iin Muyasarah; Sri Anafarhanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the perceptions, motivations, and practices of the Banjar Regency community regarding gold as an investment instrument. Using a qualitative approach through interviews with respondents from various backgrounds, it was found that the majority of the community views gold as a safe, stable, and easily liquidated asset. Gold investment is chosen because its value is resistant to inflation, can be inherited, and aligns with Islamic economic principles. The results of this study provide insight into how local traditions and socio-economic conditions shape Islamic investment patterns.